2014
DOI: 10.3138/jcfs.45.1.31
|View full text |Cite
|
Sign up to set email alerts
|

The Changes in Mainland Chinese Families During the Social Transition: A Critical Analysis

Abstract: China has seen a rapid urbanization and industrialization, and a dramatic improvement in the quality of life and living conditions since its economic reform started in 1980s. The changes in the social and economic context, and implementation of One Child Family Policy led to noticeable changes in family structure and relationship. While traditional extended families exist, there occur multiple forms of Chinese families, i.e. nuclear families, single-parent families, DINK families, the single person household a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 8 publications
(7 reference statements)
2
65
0
Order By: Relevance
“…Therefore, the loose cultural constraint on filial obligation may partially lead to the finding of insignificant association of the number of children with older couples' depressive symptoms in the United States and UK. In addition, modernization around the world also reduces filial support to older adults because adult children are focused more on their nuclear family (e.g., Aboderin, ; Xu & Xia, ). Therefore, the decreasing support from children may explain why the number of children could not bolster the older adults' mental health in the four countries.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the loose cultural constraint on filial obligation may partially lead to the finding of insignificant association of the number of children with older couples' depressive symptoms in the United States and UK. In addition, modernization around the world also reduces filial support to older adults because adult children are focused more on their nuclear family (e.g., Aboderin, ; Xu & Xia, ). Therefore, the decreasing support from children may explain why the number of children could not bolster the older adults' mental health in the four countries.…”
Section: Discussionmentioning
confidence: 99%
“…Having immigrated when South Korea and China were still developing and recovering from political turmoil, Korean and Chinese immigrants remember a traditional culture and economy that has since undergone dramatic changes. Some studies indicate that the tradition of delegating family traditions and caregiving responsibilities to the oldest son and daughter‐in‐law in cities like Seoul, Hong Kong, and Taipei may be changing rapidly with growing economic instability, the growing significance of education, changes in primogeniture and one‐child laws, and declining state support for the elderly (Fend, Poston, and Wand ; Kim and Cook ; Lee and Bauer ; Xu and Xia ). These structural changes have caused more daughters to assume more responsibilities for their parents in their old age, thus restructuring patrilocal and patrilineal traditions.…”
Section: The Emotional Dynamics Of “Doing Family”mentioning
confidence: 99%
“…The family contexts were related to health including the positive aspect, such as family support, and the negative aspect, such as family conflicts. A recent study carried out in China showed that family collectivism and mutual dependence were preferred to individualism and continued to be the dominating family values (Xu & Xia, 2014). A study by Ho, Chesla, and Chun (2012) showed the important role of the family of Chinese Americans with T2DM; the patients and their family members took on reciprocal role responsibilities in which family members demonstrated their care through coaching and being involved, and persons with diabetes reciprocated by making healthy choices.…”
Section: Discussionmentioning
confidence: 99%